ASSESSING EMERGING DIGITAL TECHNOLOGIES FOR RURAL HEALTHCARE, AGRICULTURE, AND ECO-TOURISM DEVELOPMENT - Khanna, Kanika (ShodhKosh: Journal of Visual and Performing Arts, 2023)
We examine how modern technologies influence healthcare, farming and ecological tourism in the rural region of Rohtak, Haryana. The main aim is to analyze the role of digital and intelligent technologies in making these industries better in rural areas. This research involved surveys of 120 locals from the Rohtak district. We used a well-organised questionnaire that applied both a five-point Likert scale and many multiple-choice enquiries to capture data. The analysis looks at how technology is used in healthcare, farming and to boost tourism in nature reserves. A range of statistical methods which includes descriptive statistics, chi-square tests, ANOVA, correlation and regression analysis, were used to study the obtained data. Researchers found that better technology use leads to progress in giving access to healthcare, making food systems more sustained and increasing eco-tourism. According to chi-square and ANOVA results, various demographic groups see technology in different ways. It became clear from regression analysis that technology adoption greatly influences the improvement of these sectors. Experts have found that bringing in new technologies can significantly improve rural healthcare, support farming and promote green tourism which all contribute to better rural areas.